2014
DOI: 10.1136/neurintsurg-2014-011451
|View full text |Cite
|
Sign up to set email alerts
|

Successful recanalization for acute ischemic stroke via the transbrachial approach

Abstract: The recent development of revascularization devices, including stent retrievers, has enabled increasingly higher revascularization rates for arterial occlusions in acute ischemic stroke. Patient-specific factors such as anatomy, however, may occasionally limit endovascular deployment of these new devices via the conventional transfemoral approach. We report three cases of acute ischemic stroke where a transbrachial endovascular approach to revascularization was used, resulting in successful recanalization. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“… 1 , 3) We attribute this difference in time required to advance a guiding catheter into the ICA or vertebral artery to the general increased difficulty of the transbrachial approach over the transfemoral approach in advancing a guiding catheter into the target vessels. Yet the efficacy of the transbrachial approach for AIS patients, especially in certain patient-specific cases, should also be noted as reported by Okawa et al 13) In their report, a Simmons-type catheter was later exchanged for a distal access catheter (DAC), which is larger and longer than a Simmons-type catheter. In our case it was the transfemoral approach which would have been more time-consuming; we needed the transbrachial approach to save time.…”
Section: Discussionmentioning
confidence: 78%
“… 1 , 3) We attribute this difference in time required to advance a guiding catheter into the ICA or vertebral artery to the general increased difficulty of the transbrachial approach over the transfemoral approach in advancing a guiding catheter into the target vessels. Yet the efficacy of the transbrachial approach for AIS patients, especially in certain patient-specific cases, should also be noted as reported by Okawa et al 13) In their report, a Simmons-type catheter was later exchanged for a distal access catheter (DAC), which is larger and longer than a Simmons-type catheter. In our case it was the transfemoral approach which would have been more time-consuming; we needed the transbrachial approach to save time.…”
Section: Discussionmentioning
confidence: 78%
“…approach was chosen only for patients who switched from unsuccessful TFA. [4][5][6] Haussen et al 4) reported 15 patients who underwent endovascular treatment for acute ischemic stroke via the TRA. In 12 of these, the TFA was unsuccessful, requiring a switch to the TRA.…”
Section: Resultsmentioning
confidence: 99%
“…According to several studies, the route was changed, or the use of devices was devised in such patients. [3][4][5][6]11) Of patients with pc-LVO, the prognosis becomes unfavorable in approximately 90% when recanalization is not achieved. On the other hand, recent studies indicated that the endovascular treatment related effective recanalization rate was approximately 70%-80%, and that a favorable outcome was achieved in 30%-40%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transbrachial arterial access (TBA) for both angiography and interventions has been described in the neurointerventional literature when TFA cannot be performed safely for reasons such as small radial artery/sheath size ratio or due to aortic arch or supra-aortic vessel tortuosity 61–65. The larger diameter compared with the radial artery offers the advantage of placement of larger guiding catheters and devices at a cost of an increased chance of limb ischemia due to less robust collateral circulation and increased access site complications due to its deeper location within the tissues of the brachium.…”
Section: Transbrachial Arterial Accessmentioning
confidence: 99%